Free riding and rebates for residential energy efficiency upgrades: A multi-country contingent valuation experiment - Mark Olsthoorn; Joachim Schleich; Xavier Gassmann; Corinne Faure (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2017)
The cost-effectiveness of energy technology upgrade programs critically depends on free riding. This paper assesses ex ante the effects of free riding on the cost-effectiveness of a rebate program that promotes the adoption of energy-efficient heating systems, relying on contingent valuation choice experiments carried out through identical representative surveys in eight EU Members States. The anal-ysis distinguishes between strong and weak free riders: strong free riders already plan to adopt a new heating system in the next five years; weak free riders decide to purchase once propositioned with an attractive technology package (and there-fore do not require a rebate to adopt). The reservation rebates for incentivized adopters (those who decide to adopt because of a rebate) differ substantially across countries. On average, they amount to approximately 40% of the heating system's purchasing price, suggesting generally high opportunity costs for prem-ature upgrades. The reservation rebate and weak free-ridership vary with income, risk and time preferences, and environmental identity. At a rebate level that cor-responds to half the purchase price of the offered heating system, the estimated share of free riders exceeded 50% for most countries, with a typically higher share of weak free riders than strong free riders. Specific rebate cost estimates (in exteuro/tCO2) differ considerably across countries, suggesting that cooperation can yield budgetary benefits.
urn:nbn:de:0011-n-4613797
Keywords: Q41; Q48; Q51; 330; free rider; subsidies; energy efficiency; contingent valuation